2015
DOI: 10.1371/journal.pone.0121384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acute Inspiratory Muscle Exercise on Blood Flow of Resting and Exercising Limbs and Glucose Levels in Type 2 Diabetes

Abstract: To evaluate the effects of inspiratory loading on blood flow of resting and exercising limbs in patients with diabetic autonomic neuropathy. Ten diabetic patients without cardiovascular autonomic neuropathy (DM), 10 patients with cardiovascular autonomic neuropathy (DM-CAN) and 10 healthy controls (C) were randomly assigned to inspiratory muscle load of 60% or 2% of maximal inspiratory pressure (PImax) for approximately 5 min, while resting calf blood flow (CBF) and exercising forearm blood flow (FBF) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
0
7
3
Order By: Relevance
“…The present results are not in accordance with preliminary data in six patients that we have published (Corrêa et al, 2015a). Possible explanations for this discrepancy could be the small sample size evaluated previously, and different protocols, particularly the inclusion, in the present protocol, of controlled ventilation before IME (before both loads tested, 2% and 60% of PImax).…”
Section: Discussioncontrasting
confidence: 99%
“…The present results are not in accordance with preliminary data in six patients that we have published (Corrêa et al, 2015a). Possible explanations for this discrepancy could be the small sample size evaluated previously, and different protocols, particularly the inclusion, in the present protocol, of controlled ventilation before IME (before both loads tested, 2% and 60% of PImax).…”
Section: Discussioncontrasting
confidence: 99%
“…Mice fed with HFD showed a significant increase in mean body weight as compared to other groups ( P < 0.05), whereas exercise maintained the body weight in the HFD + Ex group similar to the group fed with ND (Figure 1B ). Although exercise is reported to reduce blood glucose level (Correa et al, 2015 ), we did not find significant decrease in the level of blood glucose in HFD + Ex group (Figure 1C ). It could be due to less duration and/or intensity of exercise.…”
Section: Resultscontrasting
confidence: 71%
“…Individuals with metabolic syndrome showed no decrease in glucose after a 7-day RMT protocol (15 min, 3 times a day) at a 30% load of PImax ( 30 ). Lastly, a previous study observed that individuals with type 2 DM demonstrated a 40% reduction in glucose levels with a single high-strength RMT load (60% PImax) ( 31 ).…”
Section: Discussionmentioning
confidence: 94%